Respuesta :
Find the rate of change at x=0 and at x=3, then find the average of those values.
f(0) = 2(0) + 1 = 1
f(3) - 2(3) + 1 = 7
[tex] \frac{f(0)+f(3)}{2} = \frac{1 + 7}{2} = \frac{8}{2} = 4[/tex]
Answer: 4
f(0) = 2(0) + 1 = 1
f(3) - 2(3) + 1 = 7
[tex] \frac{f(0)+f(3)}{2} = \frac{1 + 7}{2} = \frac{8}{2} = 4[/tex]
Answer: 4
Answer:
2.
Step-by-step explanation:
We have been given the formula of a function [tex]f(x)=2x+1[/tex]. We are asked to find the average rate of change of the given function between [tex]x=0[/tex] and [tex]x=3[/tex].
To find the average rate of change we will use formula:
[tex]\text{Average rate of change}=\frac{f(b)-f(a)}{b-a}[/tex]
Upon substituting our given values in above formula we will get,
[tex]\text{Average rate of change}=\frac{f(3)-f(0)}{3-0}[/tex]
[tex]\text{Average rate of change}=\frac{2\cdot 3+1-(2\cdot 0+1)}{3-0}[/tex]
[tex]\text{Average rate of change}=\frac{6+1-(0+1)}{3}[/tex]
[tex]\text{Average rate of change}=\frac{6}{3}[/tex]
[tex]\text{Average rate of change}=2[/tex]
Therefore, the average rate of change for our given function between [tex]x=0[/tex] and [tex]x=3[/tex] is 2.